Meningkatkan Kemampuan Berpikir Kritis melalui Alat Peraga Pilogma pada Materi Logika Matematika - Lia Tuti Alawiah; Desi Rahmatina; Febrian Febrian (Jurnal Gantang, 2018)
The purpose of this study is to find out how to improve students' critical thinking skills by using props Pilogma on the material of truth value of compound logic mathematical statements. This research is a Classroom Action Research. This qualitative research was conducted by using 2 cycles and each cycle contained 2 class meetings. Researchers used observation techniques, documentation, interviews, and tests to obtain data. Data analysis techniques through the data reduction phase, data presentation and conclusion drawing and verification and triangulation of data. The subject of this research is class X of SMA Muhammadiyah Tanjungpinang. The object of research is to improve students' critical thinking ability which can be seen through test result at the end of cycle I and II and observation, documentation and interview. The results showed that students' critical thinking ability can be improved through the use of props Pilogma in learning Mathematics Logic material. Keywords: mathematical logic, critical thinking skills, props Pilogma